Effect of dodecylsulfate on trypsin and alpha-chymotrypsin. II. Characterization of soluble combinations (Revista Española de Fisiología, 1965)
The viscosimetric and electrophoretic behaviour of Solutions containing both sodium dodecylsulphate (SDS) and either trypsin or a-chymotriypsin, suggest the production of two different complexes: one of them seems to be formed when the relationship SDS/Protein cquals 0.2 (corresponding to about 20 mols DS- per mol of protein), the second complex, when the valué is higher, up to 0.4 (40 mols DS-). From these soluble, DS-Protein complexes, the corresponding free proteins can be recovered either by means of a DEAE chomatographic separation, or by adding Ba" to the Solutions, when all the DS- comes down while liberating the attached proteins. By a careful elution of the DEAE adsorbates, two dif ferent fractions are recovered : the one which comes out first from the colunin is enzimatically active, whereas the se cond fraction is inactive (probably the denatured protein). The relative proportion of the first, active fraction, diminishes as the relation ship SDS/Protein increases, or the detergent and protein contact period is longer. When the SDS/Protein valué is higher than 1.4, only inactive trypsin is recovered; with a-chymotrypsin, no activity is recovered when the valué equals 2. With casein as a substrate, SDS pro ves to be a competitive inhibitor of trypsin and a-chymotrypsin proteolytic activities. In the case of trysin the value of Ki(SDS) = 2.34 x 10-5 M the corresponding value established with a-chymo- trypsin is Ki(SDS) = 1.5 x io"s M. SDS denatures trypsin and a-chynio- trypsin in a process that seems to be a function of the SDS relative concentration and of the contact time between the detergent and the proteins.